2012
DOI: 10.1212/wnl.0b013e318278b685
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ketamine in refractory status epilepticus in children

Abstract: This study provides Class IV evidence that IV KE can be effective in treating children with RSE (no statistical analysis was done).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 10 publications
4
85
1
1
Order By: Relevance
“…Recent open-label, uncontrolled study provides Class IV evidence that intravenous ketamine might be effective and safe in treating children with RefSE. 12 In our study, ketamine was ineffective given through gastric tube in two cases without co-medication with intravenous midazolam. Recently published data suggested that some non-medication treatment such as ketogenic diet 13 or urgent surgical treatment 14 could be helpful in terminating RefSE in children, but none of our cases were treated by them.…”
Section: Discussionmentioning
confidence: 51%
“…Recent open-label, uncontrolled study provides Class IV evidence that intravenous ketamine might be effective and safe in treating children with RefSE. 12 In our study, ketamine was ineffective given through gastric tube in two cases without co-medication with intravenous midazolam. Recently published data suggested that some non-medication treatment such as ketogenic diet 13 or urgent surgical treatment 14 could be helpful in terminating RefSE in children, but none of our cases were treated by them.…”
Section: Discussionmentioning
confidence: 51%
“…When ketamine is selected for RSE treatment following prolonged SE, it maybe typically suitable after 5-6 anticonvulsants have been found to be ineffective. This treatment choice is summarized from previous successful reports [25,26,29], and the rationale for its use is based on prolonged seizure duration, decreased numbers of active GABA receptors, gradual elevation of NMDA receptor activity, and increased numbers of NMDA receptors [14][15][16]54,55].…”
Section: Dosagementioning
confidence: 99%
“…Moreover, Synowiec et al [30] found that a bolus dose of 1-2 mg/ kg, followed by maintenance at an infusion rate of 1.3 mg/kg/h (range 0.45-2.1 mg/kg/h) for 9.8 days (range 4-28 days), resulted in a successful seizure control rate of 100% (11/11). When ketamine is administered to children, we recommend a 2-3 mg/ kg bolus of ketamine every 5 min for a total of 2 administrations, followed by maintenance at a rate of 40 mg/kg/min (range 10-60 mg/kg/min) for 6.7 days (range 3-17 days) [26]. (2) Intravenous infusion: Zelier et al [31] performed continuous infusion of ketamine at 10-40 mg/kg/min for the treatment of RSE, and the seizures in all of the patients were ultimately effectively controlled (2/2).…”
Section: Intravenous Administrationmentioning
confidence: 99%
“…The bolus dose is between 0.5 and 3 mg/kg. The infusion rate varies between 1 and 10 mg/kg/h, with no effect noted below 0.75 mg/kg/h [15,17]. The duration for treatment varies between intermittent boluses and continuous infusions for up to 27 days [14, 18•].…”
Section: Ketaminementioning
confidence: 99%
“…Ketamine has been associated with tachycardia and acute elevation in blood pressure, all of which resolve after discontinuation of the drug [15,17]. It may also increase intracranial pressure (ICP), especially in unstable patients that cannot autoregulate.…”
Section: Adverse Effectsmentioning
confidence: 99%